A selection study on a laboratory-designed population of salmon lic (Lepeophtheirus salmonis) using organophosphate and pyrethroid pesticides. - Elena Myhre Jensen; Sigmund Sevatdal; Marit Jørgensen Bakke; Kiranpreet Kaur; Tor Einar Horsberg (PLoS ONE, 2017)
Resistance towards antiparasitic agents in the salmon louse (Lepeophtheirus salmonis) is a widespread problem along the Norwegian coast, reducing treatments efficacies and slowing down the envisioned expansion of Norwegian salmon production. The present study was conducted in order to assess the efficacies of two of the most widely used anti-parasitic substances-azamethiphos and deltamethrin-as well as assessing the benefit of having a resistant genotype compared to being fully sensitive when exposed to one of these substances. Atlantic salmon were exposed to a mix of salmon lice copepodids from a fully sensitive, a double resistant and a multi-resistant strain. Once the lice reached pre-adult stages, one group was exposed to 100 μg/L azamethiphos for 60 minutes, the other to 2 μg/L deltamethrin for 30 minutes, and the last was kept in a seawater control. Detached lice were collected at a series of time points following exposure, and all lice (immobilized and surviving) were analysed for both pyrethroid (sensitive "S" and resistant "R") and azamethiphos (fully sensitive "SS", heterozygous resistant "RS" and fully resistant "RR") resistance markers. We found that the efficacies of deltamethrin on parasites with genotype S and R were 70.3 and 13.2%, respectively. The overall efficacy of the deltamethrin treatment was 32.3%. The efficacies of azamethiphos on parasites with genotype SS, RS and RR were 100, 80 and 19.1%, respectively. The overall efficacy of the azamethiphos treatment was 80.4%. Survival analyses revealed that the median survival time in deltamethrin-sensitive and-resistant parasites were 16.8 and >172 hours, respectively. The differences were even more pronounced in the azamethiphos-treated group, where SS, RS and RR parasites survived for 0.26, 6.6 and >172 hours, respectively. The substantial differences in survival between sensitive and resistant lice following treatment demonstrate the ability of medicinal treatments to drive genetic selection towards a much more resistant salmon lice population within a very short time span if there is no influx of sensitive genotypes.